Moses in the bulrushes - Hutton, Warwick (New York : Aladdin Books.)
Retells the Old testament story of how the baby moses was sved from death by the Pharoah's daughter.
Keywords: Moses (Biblical leader); Bible, O. T. - biography; Moses - stories; Bible stories -- O.T.; Bible -- O.T. Stories